Use of Silver Nanoparticles in Treatment of Socially Significant Diseases; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Grigoriev M. G. Mikhail Georgievich (Biomedical Application of Materials and Biotechnology, 2016)
Title screen